FROM THE HISTORY OF AN UZBEK ACTOR - Raimqulovich, Dusanov Rakhimjon (International Journal of Psychosocial Rehabilitation, 2020)
The article provides interesting information about the genesis and stages of formation of an Uzbek actor’s theater. We all know that one-actor theater is one of the very historical types of clocks, like other theaters. There are a lot of fans who love this art form. Our historians point out that people have lived on this land for millions of years. Ancient Uzbekistan between the two rivers has gone through a unique evolutionary path in the formation of primitive society, social, economic and cultural development. The article provides the necessary references to the history of one-actor theater.